Cognitive Appraisal of Job Autonomy by Nurses: A Cross-Sectional Study - Lubaina Dawood Baig PhD Scholar; Malik Faisal Azeem PhD; Adil Paracha PhD (SAGE Publishing, 2022)
Introduction Job autonomy (JA), a task-level job resource has the potential to motivate individual behavior; it is indecisive, however, whether JA promotes or hinders extra-role behavior. Objective The study aims to examine the effect of JA on innovative work behavior (IWB) directly and indirectly through cognitive appraisal and work engagement (WE) while considering the organization type and age as control variables. Methods Self-administered questionnaires were used to collect the data from 326 nurses. SPSS and Amos 21 software was used to analyze the data. Data was collected between September, 2021 to January, 2022. Results According to the findings, JA can both stimulate and impede IWB indirectly through cognitive appraisal and WE depending on how it is appraised as a challenge and a threat (ρ = .089, p <.001); (ρ = −.038, p <.001), respectively. Conclusion The current study revealed that JA significantly influences the IWB of nurses directly and indirectly through cognitive appraisal and WE. Therefore, nursing management should find ways to influence nurse's appraisal of JA as a challenge rather than a threat to improve their extra-role behavior.